2020
DOI: 10.1007/s10867-020-09538-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the avoidance behavior of zooplankton on phytoplankton infected by free viruses

Abstract: In any ecosystem, chaotic situations may arise from equilibrium state for different reasons.To overcome these chaotic situations sometimes the system itself exhibits some mechanisms of selfadaptability. In this paper, we explore an eco-epidemiological model consisting of three aquatic groups: phytoplankton, zooplankton and marine free viruses. We assume that the phytoplankton population are infected by external free viruses and zooplankton get affected on consumption of infected phytoplankton; also the infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 60 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…They might prefer to ingest larger cells of protists, while the remaining nanoplankton and picoplankton seemed to be responsible for grazing marine bacteria and virus-like particles. Additionally, some modeling studies [ 69 , 70 ] have shown that zooplankton organisms are able to avoid virally infected phytoplankton and this, therefore, might be reflected as a negative correlation between the total zooplankton abundance/biomass and viral density. Our study and previous investigations dealing with autumn and winter Arctic zooplankton [ 29 , 30 ] highlighted the dominance of small copepods in the total zooplankton abundance, most of which are found to be omnivorous, preferring to ingest protozooplankton in the periods of low phytoplankton availability [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…They might prefer to ingest larger cells of protists, while the remaining nanoplankton and picoplankton seemed to be responsible for grazing marine bacteria and virus-like particles. Additionally, some modeling studies [ 69 , 70 ] have shown that zooplankton organisms are able to avoid virally infected phytoplankton and this, therefore, might be reflected as a negative correlation between the total zooplankton abundance/biomass and viral density. Our study and previous investigations dealing with autumn and winter Arctic zooplankton [ 29 , 30 ] highlighted the dominance of small copepods in the total zooplankton abundance, most of which are found to be omnivorous, preferring to ingest protozooplankton in the periods of low phytoplankton availability [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we review the behaviors of systems ( 1) and ( 25) by performing numerical simulations. The set of parametric values are adopted from numerous literature sources [27][28][29] and are presented in Table 1.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Biswas et al 28 presented an eco‐epidemiological model where phytoplankton are infected by free viruses and zooplankton tend to avoid infected cells in presence of susceptible one. They observed that the potency of avoidance stabilizes the system by ceasing the chaotic dynamics; at lower avoidance circumstances, the system is stable at zooplankton‐free state.…”
Section: Introductionmentioning
confidence: 99%